Phenological features and perianth color diversity of Iris pumila L. and I. scariosa Willd. ex Link in the Southern Urals - Kryukova A.V.; Abramova L.M. (Трансформация экосистем)
The article presents the study results of the seasonal development in culture of the two rare species of the genus Iris L., i.e. Iris pumila L. and I. scariosa Willd. ex Link. In the Bashkir Cis-Urals, the studied species reached the generative phase of development and bore fruit. Because of the later onset of the flowering period, the phenological phases of I. scariosa depended on the growing season conditions to a lesser extent than those of I. pumila. Blooming of one I. pumila and one I. scariosa Willd. ex Link flower lasted –6 days and 3–5 days, respectively, whereas the flowering of the entire study group of I. pumila and I. scariosa plants – 12 and 7 days on average. Colour variability of perianth in natural cenopopulations of both species in the Southern Urals (the Republic of Bashkortostan and Orenburg Oblast) was investigated as well. We identified 30 colour forms in ten cenopopulations of I. pumila, 10–12 of which were concurrently recorded in the largest ones. Violet-flowered plants dominated in the northern regions, while yellow-flowered in the south. In the two studied coenotic populations, I. scariosa had 11 forms with a similar (6–7) number of perianth colors, where violet prevailed.